Experimental research and damage analysis on the seismic behavior of ESJ-strengthened seismic-damaged RACFRST columns - Sheng Peng; Huangkai Sun; Dongping Wu; Xianqi Xie; Ben Mou (Sustainable Structures)
This study examines the seismic response characteristics of pre-damaged recycled-aggregate concrete-encased rectangular steel tube (RACFRST) columns. Four column prototypes underwent cyclic loading experiments to assess the rehabilitation effectiveness of enveloped steel jackets (ESJ) on seismically compromised members. Comprehensive analysis of hysteresis characteristics, rigidity deterioration patterns, strength degradation trends, energy dissipation mechanisms, deformation ductility, and strain distribution was performed using experimental data. A dual-parameter seismic damage evaluation framework was subsequently developed and validated through experimental measurements. Findings revealed that ESJ-retrofitted specimens demonstrated 23-37% enhancement in load-bearing capacity, 18-29% improvement in initial stiffness, and 32-45% increase in cumulative energy dissipation compared to reference specimens. The efficiency of rehabilitation demonstrated a negative correlation with prior damage severity, resulting in a 19% decline in efficacy as the initial damage index rose from 0.3 to 0.6. The proposed damage assessment model yielded indices ranging between 0.92-1.08 for retrofitted components, demonstrating strong correlation with experimental observations. This validated methodology enables quantitative seismic performance evaluation for ESJ-strengthened RACFRST structural elements in post-earthquake rehabilitation scenarios.